Risk Governance of The People's Palm Plantation Partnership Program in Bangka Regency - ARIANDHY, SHULBY (Jurnal Studi Pemerintahan, 2013)
Nowadays, partnership has become one of new forms of governance. It is noteffective for the government to handle all public services on its own because thesociety’s current situation turns to be more complex and complicated. However,there are risks inherent in every partnership. Every party involved in apartnership has each own potential risk. In the context of palm plantationmanagement partnerships, uncertainty in managing risks will lead to a numberof conflicts. Thus, it is important to pay attention to risk governance in apartnership. This study aims at describing how the risk governance is done inKKSR (Kebun Kelapa Sawit Rakyat/People’s Palm Plantation) program inBangka Regency, Indonesia. There are 3 main focuses of this study, namely theprocess, the strategy and the result of risk governance in KKSR program.Theresults show that the there are different interests among the parties involved inthe partnership which are potential to be the cause of conflicts. Furthermore, thepartnership achievement indicates that the strategy of risk governance appliedin KKSR Program initiated by the Government of Bangka Regency has givenpositive impact on each party involved in the partnership. The result of thisstudy also implies the importance of government role in the risk governanceprocess of the partnership program for public services. The government isresponsible for protecting the stakeholders’ interests, especially public interests,and also responsible for assuring that the goals of the partnership are achieved.